Parathyroid Adenoma with Multiple Bone Fractures: A Case Report - Rizal, Rizal; Kiki Achmad Rizki (HM Publisher, 2024)
Background: Parathyroid adenoma is a benign neoplasm of the parathyroid glands and can result in hypercalcemia due to excessive secretion of parathyroid hormone (PTH). This elevated PTH can have various manifestations, including bone fractures. Case presentation: We report the case of Tn. AB is a 41-year-old man with a series of recurrent bone fractures following minor traumas. Within a span of three years, he suffered from fractures in the right femur, left femur, and left humerus, which led to multiple surgeries, including total hip replacements. Further assessments showed an increased level of PTH and a suspicious lesion in the neck region. A CT scan revealed a potential parathyroid adenoma in the peritracheal region of the right side. Moreover, a Sestamibi scan confirmed an adenoma in the postero-inferior lobe of the right thyroid, consistent with Perrier type C, alongside osteoblastic processes and brown tumours. A subsequent parathyroidectomy confirmed a 2 cm diameter adenoma in the right lower parathyroid lobe. Histopathology from the excised tissue confirmed the diagnosis of parathyroid adenoma. Conclusion: Parathyroid adenomas can have significant clinical manifestations, including recurrent bone fractures, due to their metabolic effects on bone integrity. Early detection and surgical intervention can prevent complications and improve the quality of life for these patients.